Evaluating evapotranspiration rates for corn and cotton in thermo-limited climate of southwest Kansas - Piu, Umme Fatema (Kansas State University, 2022)
The declining water resources from Ogallala Aquifer in Western Kansas and strong climate warming trends provide opportunities for planting alternative crops that reduce irrigation water needs. For instance, cotton, a drought-tolerant crop that meets these requirements, has lately experienced a rapid growth from 6,500 ha in 2015 to 79,000 ha in 2021 in Kansas. As expansion of cotton and other drought tolerant crops intensifies, a thorough examination of evapotranspiration, water use, and irrigation strategies need to be considered to develop sustainable crop production. The widely used FAO-56 approach for calculating ET rates and crop coefficient has shown that crop coefficient can vary with location, thus, locally specific values need to be determined with a combination of in situ measurements and crop growth modeling. In this study, an approach was developed to estimate crop coefficient and evapotranspiration fluxes using continuous field measurements of radiation fluxes, aerial imagery, remote sensing datasets of vegetation growth, and maximum entropy production (MEP) modeling. The MEP model is based on non-equilibrium thermodynamics that allows the partition of surface radiative fluxes into (turbulent and conductive) heat fluxes as functions of field collected surface net radiation, temperature, and humidity. The MEP model is less sensitive to the uncertainty of the input data and model parameters than other models. Comparison of actual ET from MEP model and crop ET and reference ET from Penman-Monteith model yielded derivation of crop coefficient functions for corn and cotton in a thermo-limited climate of High Plains ecoregion of the United States. The approach was tested on two irrigated fields of cotton and corn in Southwestern Kansas in 2020 and 2021. The results showed cotton’s higher tolerance to heat, lower water demand, and lower ET rates as compared to corn. This makes growing irrigated cotton a viable option as sustainable crop production practice under changing climate in semi-arid regions.
Keywords: Cotton evapotranspiration; Maximum entropy production; Cotton in Kansas